2010
DOI: 10.1159/000312693
|View full text |Cite
|
Sign up to set email alerts
|

<i>FGFR1</i> Mutations in Kallmann Syndrome

Abstract: Kallmann syndrome (KS) is a heterogeneous genetic disorder that associates variable gonadotropin-releasing hormone (GnRH) deficiency with anosmia and, sometimes, other non-reproductive clinical features. X-linked recessive, as well as autosomal recessive and dominant modes of transmission have been described. The first KS-related gene to be described (KAL1) was in the X-linked form. The second gene (KAL2) was initially unexpected, as it was known to encode the fibroblast growth receptor 1 (FGFR1). Its consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…). The clinical manifestations of FGFR1 alterations are very heterogeneous since loss‐of‐function mutations in FGFR1 have been linked to Kallman syndrome [Dode et al., ; Albuisson et al., ; Villanueva and de Roux, ], hypogonadotropic hypogonadism with or without anosmia [Costa‐Barbosa et al., ; Vizeneux et al., ; Villanueva et al., ], and Hartsfield syndrome [Simonis et al., ; Hong et al., ]. Gain‐of‐function mutations in FGFR1 have also been identified in about 5% of Pfeiffer syndrome with or without craniosynostosis [Chokdeemboon et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…). The clinical manifestations of FGFR1 alterations are very heterogeneous since loss‐of‐function mutations in FGFR1 have been linked to Kallman syndrome [Dode et al., ; Albuisson et al., ; Villanueva and de Roux, ], hypogonadotropic hypogonadism with or without anosmia [Costa‐Barbosa et al., ; Vizeneux et al., ; Villanueva et al., ], and Hartsfield syndrome [Simonis et al., ; Hong et al., ]. Gain‐of‐function mutations in FGFR1 have also been identified in about 5% of Pfeiffer syndrome with or without craniosynostosis [Chokdeemboon et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…FGFR1 mutations account for approximately 10% of IHH patients. Patients with the same FGFR1 mutations can have severe hypogonadism or reversible phenotypes [50,51]. …”
Section: Etiopathogenymentioning
confidence: 99%
“…8 Here, we detected a genetic mutation of the currently reported repertoire of involved genes in five of the seven pedigrees in this study. For individual genes, it has been reported that KAL1, FGFR1, and PROK2/PROKR2 mutations account for 10-14%, 30 10%, 31 and 9% 32 of all KS, respectively. The present study is a report of the largest cohort of Han Chinese ethnic patients (an ethnic group that comprises more than 90% of the population of mainland China) with inherited KS.…”
Section: Discussionmentioning
confidence: 99%